2010
DOI: 10.1177/193229681000400326
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity C-Reactive Protein Predicts Cardiovascular Risk in Diabetic and Nondiabetic Patients: Effects of Insulin-Sensitizing Treatment with Pioglitazone

Abstract: Abbreviations: (BMI) body mass index, (CVD) cardiovascular disease, (HbA1c) hemoglobin A1c, (HOMA) homeostasis model assessment, (hs-CRP) high-sensitivity C-reactive protein, (LDL) low-density lipoprotein, (PPARγ) peroxisome proliferator-activated receptor-γ Keywords: atherosclerosis, diabetes, hs-CRP, inflammation, insulin resistance, pioglitazone AbstractSystemic inflammatory activity has turned out to play a key pathogenic role in vascular atherosclerosis, insulin resistance, and type 2 diabetes mellitus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 83 publications
(132 reference statements)
1
62
0
2
Order By: Relevance
“…It has been thought that serum hs‐CRP level leads to the development of atherosclerosis5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16. Although various new pharmacological approaches have been introduced to reduce hs‐CRP levels17, 18, 19, 20, 21, 22, 23, 24, 25, 26, there are still many cardiovascular diseases all over the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been thought that serum hs‐CRP level leads to the development of atherosclerosis5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16. Although various new pharmacological approaches have been introduced to reduce hs‐CRP levels17, 18, 19, 20, 21, 22, 23, 24, 25, 26, there are still many cardiovascular diseases all over the world.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that hs‐CRP level is associated with carotid atherosclerosis in patients with type 2 diabetes mellitus5, 6, 7, 8, suggesting that hs‐CRP is a useful marker to predict an accelerated atherosclerotic process. It has also been shown that elevated hs‐CRP levels are associated with increased cardiovascular risk9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the survey findings indicated that the adaptogen /vitamin preparation reduced stress perceptions to a greater extent than the corresponding placebo (Table 5). Elevated HS-CRP is strongly associated with an increased incidence of heart attack, stroke, type 2 diabetes and metabolic syndrome [2,12,[16][17][18][19], and the combination product used in this study significantly reduced these levels.…”
Section: Discussionmentioning
confidence: 89%
“…An association between sustained high values of CRP following AMI and adverse outcomes was first reported in 1982 [18]. The higher the maximum CRP recorded, the more severe the infarction suffered, the greater the likelihood of ventricular remodeling, the lower the ejection fraction, and the greater the risk of heart failure, heart rupture, and death [19].…”
Section: Discussionmentioning
confidence: 99%
“…CRP upregulates the expression of adhesion molecules in ECs that can attract monocytes to the site of injury [17]. In case of chronic low-intensity inflammation CRP damages the glycocalyx of vascular endothelium, causing its Dysfunction and making it more susceptible to proatherogenic factors [18].…”
Section: Inflammation and Crpmentioning
confidence: 99%